Perilaku Petani Arfak Dalam Mengadopsi Tehnologi Budidaya Kelapa Sawit Pada Program Kemitraan Dengan PTPN II Tanjung Morawa Medan Di Manokwari - Amestina Matualage; Sunarru Samsi Hariadi; Paulus Wiryono (Fakultas Pertanian Universitas Papua, 2019)
This study aims to determine the extent of the success of Arfak farmers in adopting the PTPN II Tanjung Morawa Medan partnership program and what factors influence it. The data obtained is needed to carry out development planning, especially agricultural development for Arfak farmers. The method used in this study is the survey method, with Arfak farmer respondents participating in the oil palm PIR partnership program in Manokwari taken by a phased random method of 126 respondents. The data obtained were analyzed using path analysis methods. The results obtained were the subjective norms of the peasant environment, especially traditional leaders who play an important role in shaping the behavior of Arfak farmers in adopting partnership programs with PTPN II Tanjung Morawa Medan, so that in agricultural development planning for Arfak farmers, the government needs to strengthen the capacity of traditional leaders among farmers Arfak..